Can Historical Institutionalism be Applied to Political Regime Development in Africa? - Gero Erdmann; Sebastian Elischer; Alexander Stroh (German Institute of Global and Area Studies (GIGA), 2011)
Historical institutionalism has been used to explain the emergence of democracy and dictatorship in various regions of the world, but not applied to political development in Africa. Based on the recently refined concepts of historical institutionalism, the aim of this study is to provide a framework for the analysis of the various regime types that have been established in Africa during the last two decades: democratic, hybrid and authoritarian. Surprisingly little effort has been dedicated to a historically grounded explanation of these regime types. Against a common claim that African politics is mainly driven by informal institutions or behaviours, we argue that an institution-based examination of African politics is justified. We then provide a proposition of how to link up concepts of historical institutionalism with empirical cases in Africa, within a comparative approach. Our proposition for tracing specific development paths will not be based on the regimes as a 'whole', but on the deconstruction of a political regime into partial regimes and subsequently into selected formal and informal institutions. This will allow for an empirical analysis of the different components of a regime over long periods of time, and thus for path-dependent analyses of regime development.
Keywords: 300; historical institutionalism Africa; critical junctures; path dependency; political regimes; Institutionalismus; Pfadabhängigkeit; Politisches System; Afrika